Bilateral sleeve fracture of the inferior pole of the patella in children: A case report - Li, Tangjiang; Xiang, Min; Lv, Xin; Gan, Yongqiao; Yu, Song (Frontiers in Surgery, 2022)
Background: A patellar avulsion fracture is a unique fracture type in children with an extremely low incidence rate in knee joint injuries, most of which are unilateral. Cases of simultaneous bilateral fracture are rare. Due to the physiological and anatomical characteristics of patellar sleeve fractures in children, obvious avulsed bony fragments are seldom seen with plain radiography after trauma; thus, this fracture type is often misdiagnosed or missed on first evaluation. Early diagnosis of patellar sleeve fracture is the key to successful treatment. Case report: This paper presents a case of bilateral patellar sleeve fracture in a 10-year-old girl that was missed in another hospital and treated successfully by open reduction and fixation of the osteochondral fragments after the patient was transferred to our hospital, yielding good clinical outcomes at the one-year follow-up. Conclusion: Overall, this case report described the clinical and imaging characteristics of inferior pole sleeve fractures in children and highlight clinicians’ awareness of this injury to assist in early, accurate diagnosis and reduce the incidence of misdiagnosis and missed diagnosis due to unfamiliarity.